EKONOMIS PENDIDIKAN DAN PEMBELAJARAN: ANALISIS STRATEGIS INVESTASI MODAL MANUSIA, EFISIENSI FISKAL, DAN TRANSFORMASI DIGITAL MENUJU INDONESIA EMAS 2045 - Selamat Riadi; Habib Anwar Al-Anshari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This report analyzes the dynamics of the education economy in Indonesia with a focus on the efficiency of budget allocation, the rate of return on investment, and the role of technology in transforming the learning process. The main problems identified include the escalation of education costs by 10-15% per year, inequality of digital access in the 3T region, and the low national education financial governance integrity index which is at a score of 69.5. The importance of this study lies in the urgent need to align the constitutional mandate of allocating 20% of the state budget with the quality of learning outputs relevant to the global job market. The methodology used is qualitative-interpretive synthesis and meta-analysis of secondary data from the Central Statistics Agency (BPS), the KPK Integrity Assessment Survey (SPI), and a contemporary literature study for the 2019-2025 period. The results of the study showed that education provides a significant wage premium in a monotonous manner, where university graduates have an average hourly wage of Rp33,491 compared to elementary school graduates of Rp12,260. It was also found that financial and digital literacy are key moderation factors in entrepreneurial success, especially in the female group and Generation Z. However, it requires large infrastructure investment to address the access gap. The strategic recommendations are directed at strengthening the 8+i link-and-match scheme and reforming the transparency of Education Unit Operational Assistance (BOSP) funds to optimize human capital towards the Golden Indonesia Vision 2045.